Promoting additional activity in youth soccer: a half-longitudinal study on the influence of autonomy-supportive coaching and basic psychological need satisfaction - Gjesdal, S.; Wold, B.; Ommundsen, Y. (Journal of Sports Sciences, 2019)
This study investigated the relationships between perceptions of coach autonomy support, basic psychological need satisfaction and the frequency at which youth soccer players engage in additional soccer activity outside of team sessions. We employed structural equation modelling to test a two-wave (T1 and T2) half-longitudinal study to see if basic psychological need satisfaction mediated the relationship between coach autonomy support and additional soccer activity across a competitive season. The sample consisted of 527 youth soccer players, aged 10-15 years. Results revealed moderate to strong temporal stability for autonomy, competence, relatedness and frequency of additional soccer activity. Furthermore, no support is offered for mediation as T1 coach autonomy support was not related to any of the three basic needs at T2 when accounting for their T1 levels. However, a positive relationship between T1 autonomy and T2 additional soccer activity emerged. This suggests that those who experience high levels of autonomy in the team setting at the start of the season report an increased frequency of additional activity at the end of the season. Results are discussed in light of the Self-Determination Theory and the Trans-Contextual Model.